The Course of Life of the Sexual Assault against Children: A Qualitative Study on a Sample of Registered Cases at Child Protection Centers in Dubai and Sharjah - Humaid, Helema Mohammed; Al-Hourani, Mohammed Abdel Karim (Dirasat: Human and Social Sciences, 2023)
Objectives: To highlight the basic stages of sexual abuse, in terms of causes, consequences and effects on the victim and people around them. Methods: The study involved 28 victims aged 4 to 18 from child protection centers in Dubai and Sharjah. It utilized a qualitative life path approach, conducting in-depth interviews with both individual cases and those with their families present. Results: Results showed that sexual abuse emerged in three main stages. The first developmental stage, results showed that the more victims close to the abuser, the higher the likelihood of sexual abuse. The second developmental stage, results showed that most of the victims were their guardian either busy when the abuse happened or was there but far away a bit from the victim. The third developmental stage, results showed that most of the victims suffered from various symptoms which are psychological, emotional, and behavioral. Results of the demographic characteristics of the respondents showed that the younger age group are the most vulnerable to sexual abuse, and most victims come from stable families and live with both parents. Conclusions: We conclude that sexual abuse is gradually growing within three basic stages: In the initial stage, abusers use manipulation, like coercion and threats, to engage in sexual activities with the victim. The second stage involves familiar activities, such as playing and gift-giving, while the abuser normalizes their behavior to the victim. The third stage underscores the importance of positive parental support in aiding victims’ recovery.